2022
DOI: 10.3390/ma15103582
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Washability of Roasted Suspended Siderite Ores

Abstract: Steel is one of the most important industrial materials, which mainly comes from the smelting of iron ore. In view of the huge steel consumption every year, the exploitation of vast reserves of siderite ores is significant for improving the self-sufficiency rate of iron ore resources and ensuring the strategic security of the iron and steel industries. This paper investigated the influence of temperature, time, and other parameters on the magnetic properties of roasted siderite ores using the method of suspend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The iron mineral transformation pattern, reaction kinetics, and magnetic separation of siderite by magnetization roasting have been systematically investigated in previous studies [2][3][4][5]. These results confirmed that siderite could be efficiently magnetized by calcination at 600-800 • C for 3-10 s in a reducing atmosphere, and magnetite could be effectively collected by the multiprocess weak magnetic separation method [7,[11][12][13]. Existing studies have confirmed the feasibility and advantages of suspended-state magnetization roasting technology (e.g., fast reaction, good magnetization effect, mature process equipment, etc.).…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…The iron mineral transformation pattern, reaction kinetics, and magnetic separation of siderite by magnetization roasting have been systematically investigated in previous studies [2][3][4][5]. These results confirmed that siderite could be efficiently magnetized by calcination at 600-800 • C for 3-10 s in a reducing atmosphere, and magnetite could be effectively collected by the multiprocess weak magnetic separation method [7,[11][12][13]. Existing studies have confirmed the feasibility and advantages of suspended-state magnetization roasting technology (e.g., fast reaction, good magnetization effect, mature process equipment, etc.).…”
Section: Introductionsupporting
confidence: 60%
“…When the roasting temperature was >750 • C, an increase in the roasting temperature caused the magnetite diffraction peak in intensity to decrease slightly. When the roasting temperature was 800 • C, FeO was detected in the roasted ore, indicating that the overreduction was responsible for decreased magnetite content [11]. As shown in Figure 5, FeCO3 and white mica underwent noticeable decomposition reactions after magnetization roasting, whereas quartz showed no obvious changes.…”
Section: Effect Of Temperature On Iron Extraction From Low-grade Side...mentioning
confidence: 96%
See 3 more Smart Citations